KNOWLEDGE, ATTITUDES AND PRACTICES TO LIFESTYLE RISK FACTORS FOR CORONARY HEART DISEASE (CHD) AND DIABETES AMONGST SOUTH ASIANS IN NORTH KIRKLEES, ENGLAND A FOCUS GROUP STUDY: Lifestyle Risk Factors for Coronary Heart Disease - Siddiqui, Farah Rashid; Rahman, Mahmood-ur-; Bhatti, Muhammad Ayaz; Mirza, Inam-ul-Haq; Shahid, Afshan (Pakistan Armed Forces Medical Journal, 2008)
Objective: The aim of the study was to identify and explore main issues relating to knowledge, attitudes and practices to lifestyle risk factors for coronary heart disease (CHD) and Diabetes amongst South Asians in North Kirklees, UK.Design: A comparative study.Place and duration of study: The study was conducted in North Kirklees, UK from April 2001 to March 2002. Material and Method: A focus group approach from qualitative research methodology was used. South Asians already attending community centers for different activities were selected randomly. Group discussions were taped and translated. Main issues were identified by analyzing these transcripts using qualitative methodology. Results: A variety of attitudes and different levels of knowledge and practices to lifestyle risk factors for coronary heart disease (CHD) and Diabetes have been observed. The main issues identified were language barrier, lack of individually tailored information, cultural and religious barriers such as lack of women-only facilities. Other barriers which have been highlighted by the study were diet, lack of physical activity and stress. Stress has also been identified as an important cause of CHD leading to Diabetes especially in South Asians (SA). Conclusion: The health care professionals need to be aware of knowledge, attitudes and culturally sensitive issues of South Asians to potential diseases in order to undertake effective preventive measures by avoiding being prejudice. Inspite of provision of communication assistants South Asians still face problems accessing health and leisure services due to language barriers. The issue of stress amongst South Asians needs to be recognized as an important issue. Hence it is important to assess the health and social needs of SA independently in order to deliver high quality and effective health care.